Ethical Traditions of Adyghe: Genre Criteria and Main Motives - Z. Zh. Kudaeva; K. N. Paranuk; A. P. Golodova (Научный диалог)
The task is to study ethical legends considered as one of the specific genre varieties of the Adyghe historical prose. The relevance of the research is due to the urgent need to create a genre classification of the Adyghe non-fairytale prose. It is noted that in this regard, the study of ethical traditions is one of the necessary stages in solving this problem. The main goal of the article is to determine genre features and main functions, to identify the main motives and images inherent in ethical legends. Cultural-historical and comparative-historical research methods are used. The socio-historical conditions and factors that contributed to the emergence of the genre of ethical legends are analyzed, various groups of legends are identified, the process of transformation of moral and ethical principles and norms is traced, the most productive plot-forming motives are determined. It is shown that the differentiating feature of ethical traditions is their cognitive and socioregulatory functions. It is argued that their main goal is to represent ideal forms and standards of interpersonal behavior, which should contribute to the formation and approval of moral, ethical and etiquette norms that existed in the Adyghe traditional society.